2017
DOI: 10.1186/s13229-017-0130-3
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging blood serotonin as an endophenotype to identify de novo and rare variants involved in autism

Abstract: BackgroundAutism spectrum disorder (ASD) is one of the most highly heritable neuropsychiatric disorders, but underlying molecular mechanisms are still unresolved due to extreme locus heterogeneity. Leveraging meaningful endophenotypes or biomarkers may be an effective strategy to reduce heterogeneity to identify novel ASD genes. Numerous lines of evidence suggest a link between hyperserotonemia, i.e., elevated serotonin (5-hydroxytryptamine or 5-HT) in whole blood, and ASD. However, the genetic determinants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 74 publications
1
33
0
1
Order By: Relevance
“…We therefore assessed the serotonin (5-HT) concentration in wt and kdm5 K6801/10424 flies. Similar to the findings in ASD patients (Chen et al, 2017), we observed that the abdomens and gut kdm5 K6801/10424 flies had significantly higher levels of 5-HT compared to wt flies ( Figures 4O and S8L). Interestingly, heads and guts of flies with intestine-specific KDM5 knockdown also showed elevated levels of 5-HT ( Figures 4R and S8M).…”
Section: Manipulation Of Gut Microbiome Rescues Kdm5-deficiency-inducsupporting
confidence: 86%
“…We therefore assessed the serotonin (5-HT) concentration in wt and kdm5 K6801/10424 flies. Similar to the findings in ASD patients (Chen et al, 2017), we observed that the abdomens and gut kdm5 K6801/10424 flies had significantly higher levels of 5-HT compared to wt flies ( Figures 4O and S8L). Interestingly, heads and guts of flies with intestine-specific KDM5 knockdown also showed elevated levels of 5-HT ( Figures 4R and S8M).…”
Section: Manipulation Of Gut Microbiome Rescues Kdm5-deficiency-inducsupporting
confidence: 86%
“…Peripheral hyperserotonemia was the earliest demonstrated neurochemical change in individuals with autism spectrum disorders (ASD) (Schain and Freedman ) and has since become the best replicated biomarker, as recent meta‐analyses conclude that hyperserotonemia is present in 25–45% of the autism population (Gabriele et al ; Chen et al ; Eissa et al ). Furthermore, whole blood maternal serotonin levels during pregnancy are associated with altered cognitive abilities and core neurodevelopmental outcomes in offspring with ASD (Montgomery et al ).…”
mentioning
confidence: 99%
“…We hypothesize that autism risk genes have distinct spatiotemporal expression signatures in developing human brain in neurotypicals. When comparing A-risk to other metrices or methods in prioritizing risk variants, we observed better performance of A-risk in prioritizing candidate risk variants using de novo variant data of 8838 trios from recent publications [6,[20][21][22][23][24]. Furthermore, we showed that A-risk and gene mutation intolerance metrics [25] can be combined to improve prior estimation in an empirical Bayesian model and enables identification of additional novel risk genes.…”
Section: Introductionmentioning
confidence: 82%
“…To investigate if A-risk can prioritize de novo risk variants detected from exome or genome sequencing studies, we compiled de novo likely gene-disrupting (LGD) variants of 8838 trios from recent published studies [6,[20][21][22][23][24] ( Supplementary Table 5). We calculated enrichment rate of LGD de novo variants in a gene set by the observed number of variants divided by the expected number estimated from background mutation rate models [35,36] ( Table 1).…”
Section: A-risk Improves Prioritization Of De Novo Variants In Autismmentioning
confidence: 99%
See 1 more Smart Citation